2005
DOI: 10.1177/0091270005274550
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile of the Oral Direct Thrombin Inhibitor Dabigatran Etexilate in Healthy Volunteers and Patients Undergoing Total Hip Replacement

Abstract: Dabigatran etexilate is an oral low-molecular-weight direct thrombin inhibitor. Following oral administration, dabigatran etexilate is rapidly converted to its active form, dabigatran. The authors investigated the absorption, distribution, and elimination of a single 150-mg dose capsule formulation of dabigatran etexilate in healthy volunteers and patients undergoing total hip replacement. In an open-label, 3-way crossover study, dabigatran etexilate was administered to 18 male volunteers in the fasted state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
237
2
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(257 citation statements)
references
References 11 publications
6
237
2
12
Order By: Relevance
“…Onset of action is prompt, it has a consistent anticoagulant effect. The half-life ranges between 12 and 17 h [40] but since kidney excretion accounts for 85% elimination , half-life does increase significantly also in patients with moderate renal failure ( creatinine clearance < 50 ml/min ).…”
Section: Anti Thrombin Agentmentioning
confidence: 99%
“…Onset of action is prompt, it has a consistent anticoagulant effect. The half-life ranges between 12 and 17 h [40] but since kidney excretion accounts for 85% elimination , half-life does increase significantly also in patients with moderate renal failure ( creatinine clearance < 50 ml/min ).…”
Section: Anti Thrombin Agentmentioning
confidence: 99%
“…All these agents are synthetic low-molecular-weight compounds that act as direct, selective and reversible inhibitors of a specific step in the coagulation cascade [41][42][43][44][45][46][47]. The anticoagulant effect of these agents is more predictable compared to that of heparin or vitamin K antagonists, allowing their administration in fixed doses without the need for laboratory monitoring or dose adjustment.…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…36 Dabigatran has a terminal halflife (t ½ ) of about 12-17 hours (Table 1). [36][37][38] Time curves for assays of antithrombotic activity, including activated partial thromboplastin time and thrombin and ecarin clotting times parallel plasma concentration-time curves, with values increasing rapidly and dose-dependently. The activated partial thromboplastin time assay can provide a useful qualitative assessment of anticoagulant activity but is less sensitive at supratherapeutic dabigatran levels.…”
Section: Pharmacology Of Dabigatranmentioning
confidence: 99%
“…38,41 Dabigatran is not metabolized by hepatic cytochrome P450 isoenzymes, does not affect the metabolism of other drugs that utilize this system, and has a low potential for drug-drug interactions. [42][43][44] Preclinical and clinical studies have shown that dabigatran etexilate, but not dabigatran, is a P-glycoprotein substrate and its bioavailability may be altered by P-glycoprotein inhibitors or inducers.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%